Efficacy of mechanical debridement with adjunct antimicrobial photodynamic therapy against peri-implant subgingival oral yeasts colonization: A systematic review and meta-analysis - Dena Ali; Jenna Alsalman (Photodiagnosis and Photodynamic Therapy)
Background: It is hypothesized that mechanical debridement (MD) with adjunct antimicrobial photodynamic therapy (aPDT) is more efficient in reducing peri-implant subgingival yeasts colonization (SYC) than MD alone. The aim of the present systematic review and meta-analysis was to evaluate randomized controlled trials (RCTs) that assessed the efficacy of MD with and without adjunct aPDT towards the reduction in peri-implant SYC. Methods: The focused question was “Is MD with adjunct aPDT more effective then MD alone in reducing peri-implant SYC?” Indexed databases were searched without time and language restrictions until February 2024. The Population/Patients, Intervention, Control, Outcome (PICO) strategy was adopted. The literature search was performed using the preferred reporting items for systematic reviews and meta-analysis guidelines. The risk of bias (RoB) was assessed using the Cochrane RoB tool. Results: Three randomized controlled trials with a follow-up duration of 90 days were included and processed for data extraction. In one study, all participants were male and in the remaining two studies, males and females were included. One study showed that peri-implant MD with adjunct aPDT is more effective in reducing SYC than MD alone. In another study, there was no significant difference in SYC following MD with or without adjunct aPDT. In one study, the role of peri-implant MD with adjunct aPDT remained unclear due to missing data. The overall RoB was high and low in one and two studies, respectively. Conclusion: The role of MD with or without adjunct aPDT in reducing peri-implant SYC remains debatable.